Nesting Ecology and Reproducing Females of the Snail-eating Turtle, Malayemys macrocephala, in Paddy Fields in Central Plain of Thailand - Visoot, Yupaporn; Ngamprasertwong, Thongchai; Kitana, Noppadon (Tropical Natural History, 2021)
The Malayan snail-eating turtle, Malayemys macrocephala, is a common freshwater turtle that is distributed in the central plain of Thailand. The turtle is well adapted to agricultural areas, making them vulnerable to population decline as their nesting grounds are not in protected areas. This study aimed to examine the nesting ecology and estimated number of reproductive females. Nests of M. macrocephala were surveyed in a 16-hectare rice field at central Thailand. Turtle nests were searched for and monitored on two consecutive days per fortnight during December 2013 to May 2014. The nesting season of M. macrocephala in this area was from early December to early April. A total of 74 clutches of 3–9 eggs each were found in this area. Turtle nests were covered by ground vegetation and mainly found on the rice-field ridge with the distance less than 5 m from the water source. All the turtle eggs were collected for incubation at the laboratory until hatching. In addition, adult turtles were trapped by mesh traps placed in canals within the study area. Mitochondrial DNA samples of juvenile turtles and trapped adult females were analyzed for haplotype variation in the cytochrome b gene. From 71 clutches and six adult females found within this study period, seven haplotypes were found. This indicates that seven or more females reproduced. Given the assumption that a reproductive female lays only one clutch per night, eggs with the same haplotype in multiple new nests in one night were laid by different females. Based on this, our field records of newly formed nests revealed that at least 10 different females reproduced in this 16-hectare area. Our results show that combining field and molecular techniques allows for determining a minimum number of female turtles that reproduce in a particular area, which is useful for conservation planning in the future.